Recyclable polyaspartate-coated magnetic nanoparticles for sustainable control of calcite and barite scales in oilfield operations - Abdelrahman T. Abdelaal (14674629) (2026)
Scale formation is a major challenge in hydrocarbon production, leading to decreased efficiency, equipment damage, and increased operational costs. Conventional chemical inhibitors used to prevent scaling are often non-recyclable and generate continuous chemical discharge, raising environmental concerns. In this study, a green, recyclable nanocomposite composed of a magnetite core coated with trisodium citrate and polyaspartate (Fe3O4@TSC@PASP) was developed for sustainable control of calcite (CaCO3) and barite (BaSO4) scales. Static jar tests show that Fe3O4@TSC@PASP achieves complete calcite inhibition at ≥20 ppm and exhibits performance trends that closely match free PASP when normalized to the active-polymer dose. Dynamic tube-blocking tests at 100 °C and 1000 psi further confirm effective scaling suppression for 60 min at 50 ppm, demonstrating that immobilization of PASP on a magnetic carrier preserves its intrinsic inhibitory function while enabling recyclable deployment not achievable with free PASP. SEM imaging revealed pronounced distortion of calcite and barite morphologies, while calcium-compatibility assessments confirmed high stability across salinity and Ca2+ levels relevant to field environments. The nanocomposite retained full inhibition efficiency over four magnetic recovery cycles, confirming its technical feasibility for reuse. This work introduces a distinct design strategy in which PASP is immobilized on a magnetically responsive platform, providing mechanistic insight into polymer–nanoparticle synergy and establishing a practical pathway toward recyclable, environmentally responsible scale-management technologies for the energy sector. Other Information Published in: Journal of Water Process Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jwpe.2025.109372